Tinjauan Fikih Terhadap Akad Jual Beli Terhadap Suatu Objek Benda Tanpa diikuti Pemindahan Kepemilikan - Rizki, Raden Hasnan Muhamad (CV Widina Media Utama, 2024)
Akad is a relationship or meeting of consent and acceptance which results in the emergence of law. Ijab is an offer submitted by one of the parties, and kabul is the answer to the agreement given by the partner in response to the first party's offer. The sale and purchase agreement is considered valid if there is an agreement between the two parties which is carried out with words and gestures. Buying and selling is one of the muamalah activities that many humans do. The Qur'an explains that buying and selling is lawful while Allah forbids usury. Buying and selling is the exchange of property with assets in the form of transfer of property and ownership which focuses on the words